The Reproducibility of Heart Rate Recovery after Treadmill Exercise Test - Tulumen, Erol (Ann Noninvasive Electrocardiol, 2011)
Background: Although predictive value of heart rate recovery (HRR) has been tested in large populations, the reproducibility of HRR in treadmill exercise test has not been assessed prospectively. This prospective study examined whether HRR index has test–retest stability in the short term. Methods: A total of 52 healthy volunteers without cardiovascular risk factors (mean age, 30 ± 10 years, 30 females) underwent standardized graded treadmill exercise test, and the test was repeated on the 7th and the 30th days. The subjects’ maximal heart rates and the decrease of heart rate from the peak exercise level to the level of 1, 2, 3, 4, and 5 minutes after the termination of the exercise were examined on each test, and heart rates for each minute from the first, second, and third tests were compared for each individual. Results: The maximal heart rates on the 1st, 7th, and the 30th days were 179 ± 11, 177 ± 10, 178 ± 10 beats/min, respectively [P = 0.07, intraclass correlation coefficient (ICC) = 0.92], and the 1st minute HRR indices after peak exercise were 33 ± 10, 33 ± 10, 33 ± 11, respectively (P = 0.66, ICC = 0.88). There was no statistical difference in the 2nd, 3rd, 4th, and 5th minute heart rates of the recovery phase among the 1st, 7th, and 30th day treadmill exercise tests, either. Conclusion: Maximal heart rates and the decline of heart rate to the 5th minute on recovery phase after treadmill exercise test have short‐term reproducibility. Ann Noninvasive Electrocardiol 2011;16(4):365–372